Pola Perlindungan Anak dalam Dimensi Sekolah Ramah Anak di Sekolah/Madrasah Kota Mataram - Edy Herianto; Mursini Jahiban; Dahlan Dahlan (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2020)
The main problem examined through this research is what is the pattern of child protection in the dimension of child-friendly schools in schools/madrasahs in Kota Mataram, Provinsi NTB? Research data were collected through interview techniques, observation, documentation, and focus group discussions with principals, teachers, committees, school supervisors, and students. Purposely, the research data sources were determined to come from 4 schools/madrasahs. All data collected were then analyzed qualitatively. The results show that (1) the regulation of child-friendly school/madrasah policies, development strategies and their implementation is based on the prevailing laws and regulations regarding child protection in the dimension of child-friendly schools. (2) Implementation of child protection programs in the dimension of child-friendly schools in Kota Mataram is based on planning, organizing, implementing, and supervising. (3) There are two factors, namely internal and external, which determine the success of the child protection program in the dimension of child-friendly schools in schools/madrasahs in Kota Mataram.